Frank’s Criticism toward Nazism as Seen from the Lives of the Characters in The Diary of a Young Girl - Adria Vitalya Gemilang (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This research is analyzing a diary by Anne Frank. It tells the readers about the lives of the Jews during the Nazi occupation. The diary describes the experiences of the Jews in order to survive during Nazism. It tells how the Jews are discriminated and suffered by Nazism. Anne Frank describes their everyday life vividly and in honest way which brings the readers to understand their experiences without experience it. The objective of this research is to identify Frank’s criticism toward Nazism as seen from the lives of the characters. In order to accomplish the objectives, the library research is used since many data and theories are collected from some books. In order to analyze the problem, the writer employs the sociocultural-historical approach. It is used to identify criticism toward Nazism. The result of the analysis shows that there is Frank’s criticism toward Nazism in the description of the lives of the characters under the Nazis occupation. Through her diary, Anne Frank criticizes the discrimination, the lack of education, the hunger, the chaos and the mass killing during the reign of Nazism in the Netherlands.